2018
DOI: 10.1002/fuce.201700190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Passive Anion‐Exchange Membrane Micro Fuel Cell Using Glycerol from Several Sources

Abstract: This paper addresses energy generated in a passive anion‐exchange membrane micro fuel cell (PAEMμFC) using glycerol from several kinds of sources: high‐purity glycerol (HPG), saponification process‐derived glycerol (SPDG), crude glycerol from sunflower oil biodiesel (CGSOB) and crude glycerol from cooking oil biodiesel (CGCOB). Spectrophotometry, volumetric Karl Fischer, gas chromatography, calorimetry, Fourier transform infrared, and cyclic voltammetry were employed for the glycerol samples characterization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…This design was matched on the design previously reported [18]. Catalytic mixtures were elaborated using AuNPs and Pt/C, as anode and cathode, respectively, as follows: First, for the preparation of the platinum mixture, for each gram of this catalyst 73 µL of isopropyl alcohol and 7 µL of Nafion were added and were mixed homogeneously using a vortex and subsequently sonicated for 20 minutes [19]. On the other hand, for the preparation of the AuNPs mixture; 10 mg of each EF previously described in this section (EFC, EFMD, EFPD and EFS) were mixed with carbon Vulcan (XC-72) and 20 µL of Nafion.…”
Section: Methodsmentioning
confidence: 99%
“…This design was matched on the design previously reported [18]. Catalytic mixtures were elaborated using AuNPs and Pt/C, as anode and cathode, respectively, as follows: First, for the preparation of the platinum mixture, for each gram of this catalyst 73 µL of isopropyl alcohol and 7 µL of Nafion were added and were mixed homogeneously using a vortex and subsequently sonicated for 20 minutes [19]. On the other hand, for the preparation of the AuNPs mixture; 10 mg of each EF previously described in this section (EFC, EFMD, EFPD and EFS) were mixed with carbon Vulcan (XC-72) and 20 µL of Nafion.…”
Section: Methodsmentioning
confidence: 99%
“…As the power output of the device was affected by GDL morphological defects and AEM stabilities, in addition to MEA manufacturing, further investigations of the alkaline fuel cells are needed to address this problem, since it is vital for the long-term operation of PS-DGFCs. In line with this necessity, Olivares-Ramírez et al [169] reported a study focused on the evaluation of the energy generated in AEM-based PS-DGFCs using glycerol from different sources, namely, high-purity glycerol (HPG), saponification process-derived glycerol (SPDG), crude glycerol from sunflower oil biodiesel (CGSOB), and crude glycerol from cooking oil biodiesel (CGCOB). The device used was assembled by sandwiching the MEA between two epoxy-based SU-8 CCs and placing them between two PMMA pieces.…”
Section: Other Alcoholsmentioning
confidence: 99%
“…Figure 17. Schematic drawing showing the cross-section of the assembled AEM-based PS-DGlyFC.Reproduced from[169] with permission from John Wiley and Sons 2019.…”
mentioning
confidence: 99%
“…As previously reported, crude GLY is more than four times cheaper than refined GLY, but ADGFC tests reported in Table 4 were generally carried out using high purity glycerol as the fuel. In some cases, however, the performance of ADGFC fueled with refined GLY was compared to that ADGFC fuel with crude GLY [33,54,129,136]. Zhang et al [33] compared the performance of ADGFCs with different anode catalysts (Pt/C, Pd/C and Au/C) fueled with pure GLY to that of the corresponding ADGFC fueled with crude GLY.…”
Section: Adgfcs For Energy Productionmentioning
confidence: 99%